Fish for food security in Yemen: Insights from the Data in Emergencies survey - Dey, Durjoy; Belton, Ben; Kurdi, Sikandra; Ecker, Olivier (International Food Policy Research Institute, 2026)
Fish is the most frequently consumed animal-source food in Yemen, apart from dairy. Fish consumption is highest in coastal southern Yemen but also very common in southern inland districts. Nine percent of households in coastal southern Yemen earned income from fishing. Earning fishing income is highly positively associated with consumption of fish or meat and with the frequency of fish or meat consumption. Sustaining fish stocks and fishing livelihoods is critical to food security and nutrition in southern Yemen.